A NIR fluorescent probe for detection of viscosity and lysosome imaging in live cells. Issue 26 (18th June 2019) - Chen, Tong; Chen, Zikang; Liu, Ruiyuan; Zheng, Shaobing
Abstract : A D–π-A structure near-infrared fluorescent probe (Lyso-BTC) is explored for its fluorescence visualization and detection of lysosomes in view of a large Stokes shift (∼190 nm), NIR emission (685 nm), excellent photostability, fluorescence response to viscosity, and lysosome-targeted property. Abstract : Lysosomes, as the cellular recycling center, are filled with numerous hydrolases that can degrade most cellular macromolecules. Studies have shown that the abnormality of viscosity in lysosomes will disrupt the normal function of lysosomes. Herein, a D–π-A structure near-infrared fluorescent probe containing N, N -dimethylamino benzene as an electron donor, benzothiozole as an electron acceptor, and a vinyl group as a π unit, Lyso-BTC, is explored for fluorescence imaging of lysosomes and detection of lysosomal viscosity changes. Lyso-BTC exhibits a large Stokes shift (∼180 nm), NIR emission (685 nm), good biocompatibility, excellent photostability, and fluorescence response to viscosity. Moreover, the results of in vitro studies reveal that Lyso-BTC is lysosome-targeted and could be applied for the detection of viscosity changes in lysosomes caused by chloroquine treatment. These results confirm that Lys-BTC could be employed to monitor lysosomal viscosity changes in living cells.